2003
DOI: 10.1152/ajpendo.00114.2002
|View full text |Cite
|
Sign up to set email alerts
|

Acute lowering of circulating fatty acids improves insulin secretion in a subset of type 2 diabetes subjects

Abstract: Qvigstad, Elisabeth, Ingrid L. Mostad, Kristian S. Bjerve, and Valdemar E. Grill. Acute lowering of circulating fatty acids improves insulin secretion in a subset of type 2 diabetes subjects. Am J Physiol Endocrinol Metab 284: E129-E137, 2003; 10.1152/ajpendo.00114.2002.-We tested the effects of acute perturbations of elevated fatty acids (FA) on insulin secretion in type 2 diabetes. Twenty-one type 2 diabetes subjects with hypertriglyceridemia (triacylglycerol Ͼ2.2 mmol/l) and 10 age-matched nondiabetic subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
3
18
0
2
Order By: Relevance
“…However, in the present study, the enhanced insulin sensitivity of type 2 diabetic patients after acipimox treatment strongly correlated with decreases in plasma FFA and intramyocellular LCFA-CoA concentrations, suggesting that the reduction in plasma FFA levels is the predominant mechanism for the acipimox-induced improvement in insulin sensitivity. Consistent with the results of the present study, Qvigstad et al (52) recently demonstrated that the acipimox-induced enhancement in insulin sensitivity was reversed with the infusion of intralipid/heparin in type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the present study, the enhanced insulin sensitivity of type 2 diabetic patients after acipimox treatment strongly correlated with decreases in plasma FFA and intramyocellular LCFA-CoA concentrations, suggesting that the reduction in plasma FFA levels is the predominant mechanism for the acipimox-induced improvement in insulin sensitivity. Consistent with the results of the present study, Qvigstad et al (52) recently demonstrated that the acipimox-induced enhancement in insulin sensitivity was reversed with the infusion of intralipid/heparin in type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…Intralipid-induced ␤-cell dysfunction was not evident, however, in subjects with established type 2 diabetes (15), presumably because of the preexisting profound ␤-cell impairment. Consistent with these results, other authors have found that lowering of fatty acids improved GSIS only in diabetic patients having the lowest levels of Hb A 1c (72). In our study (15), those with established diabetes actually showed an increase in absolute GSIS vs. controls, which is similar to our finding in prediabetic ZDF rats with mild hyperglycemia (33).…”
Section: Lipid-induced ␤-Cell Dysfunction In Obese and Diabetic Animasupporting
confidence: 92%
“…Hyperglycemic clamp-derived measures of insulin secretion were unchanged after acipimox was administered (45). However, with the use of nicotinic acid and lipid/heparin infusions, two other studies showed that decreases in plasma FFA levels were associated with reductions in basal and glucose-stimulated insulin secretion (7,13).…”
Section: Discussionmentioning
confidence: 99%
“…Our aim was to explore whether a prolonged fast would increase plasma FFA levels sufficiently to study the effect of elevated levels on the glucose-stimulated acute insulin response (AIR) and S I and whether any potential effects could be reversed by lowering FFA levels with the antilipolytic drug acipimox (7,13,45). We studied 14 healthy volunteers without a family history of diabetes to test the hypothesis that increased plasma FFA levels are directly linked to changes in AIR and S I .…”
mentioning
confidence: 99%